A study on comparison of cerviprime and IV oxytocin in labour induction and evaluation of changes in the bishop’s score with these two agents - Swapna, Durvasula Lakshmi; Sree, Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: There are several strategies for the induction of labor (IOL), and pharmacologic agents, including oxytocin and prostaglandins, are most commonly used in clinical practice. Compared with oxytocin, the prostaglandin E2 agent, dinoprostone, has been regarded as moreeffective for the induction of labor of LTPs with a non-dilated cervix. Objective was to compare the PGE2 gel placed intracervically with that of oxytocin given intravenously for induction of labor in both primipara as well as multipara with the comparison of Bishop’s score at the starting of induction and its improvement with both of these inducing agents in those with indications for induction with gestational age greater than 36 weeks. Methods: Hospital based prospective observational study over a period of one year on patients attending the antenatal and high-riskpregnancy clinic and scheduled for induction of labor with Bishop score <4. Results: The number of successful induction was low in primiparae group with low Bishop’s score (1-2). There were greater number of successful inductions in both primi as well as multiparae with higher Bishop’s score. Conclusions: When a primigravida had a low cervical score or an unfavourable cervix, intracervical PGE2 gel was found to be more effective at ripening the cervix and inducing labour. Both medicines were equally effective at inducing labour in cases of multigavidae with any Bishop’s score and primi with a higher Bishop’s score.